Parametric geometry and CFD process for turbofan nacelles - Heidebrecht, Alexander; Stańkowski, Tomasz; MacManus, David G. (American Society of Mechanical Engineers (ASME), 2016)
A parametric geometry definition for a generic turbofan nacelle was developed for use in preliminary design, based on Class-Shape Transformation curves. This takes as input a set of six intuitive variables which describe the main dimensions of a nacelle. This set is the same set of inputs as required by a preliminary nacelle design method to which the aerodynamic properties of resulting shapes were compared. An automated computational fluid simulation process was developed and implemented which generates meshes and quickly conducts an analysis of the resulting nacelle shapes using a commercial code. Several geometries were generated and analysed using this process to show whether the aerodynamic properties of the generated shapes are in line with the expected performance of a fan cowl of equal dimensions. It was found that the aerodynamic performance of the parametric fan cowls significantly exceeds predictions from an established preliminary fan cowl design method and is very close in performance to existing designs. The drag of an equivalent parametric fan cowl can therefore be used as a predictor of nacelle performance with greater accuracy than established preliminary design methods. It is therefore suited as a tool to develop improved preliminary design methods, and for studies of the design space for preliminary nacelle design.